Compound Coastal Flood Risk and Infrastructure Loss Estimation in Bengkulu City, Indonesia, under Sea-Level Rise Using Google Earth Engine and OpenStreetMap - Fitriansyah, Aidil; Fikri, Muharram Nur (Science and Technology Research Centre, Universitas PGRI Semarang, 2026)
Bengkulu City, Indonesia, is facing increasing risks due to sea-level rise (SLR), yet risk assessments based on regulations are still absent for secondary coastal cities. This study models the compound flood hazard for three scenarios (+1.28 m, +2.13 m, +3.00 m) using Google Earth Engine, GIS and OpenStreetMap, to produce inundation zones of 12.64–77.76 ha. The five-class risk map generated by the Coastal Vulnerability Index weighted by AHP (CR = 0.016) covers 1,058.83 ha. Under Scenario B (2100, SSP5-8.5), the infrastructure exposure includes 22 buildings and 9.33 km of roads. Public facilities are excluded from the quantitative loss estimation because the buffer sensitivity analysis (200–1,000 m) shows 333–335 of 336 city amenities at all distances, indicating non-discriminating coverage. Confirmed direct replacement losses based on Kepmen PUPR No. 943/KPTS/M/2024, SE DJBK No. 68/2024 and Bengkulu IKK = 94.20, total IDR 47.1–102.0 billion across scenarios (Scenario B: IDR 86.1 billion). The loss due to annual maintenance is IDR 896 million/year (Pergub Bengkulu No. 25/2025). The regulation-compliant approach is transferable to other Indonesian secondary coastal cities as long as the site-specific VLM assessment is performed.